Effect of soil solarization and methyl bromide on the soil fungi community - Venâncio, Wilson Story; Bueno, César Júnior; De Souza, Nilton Luiz [UNESP] (My University, 2006)
Soil microbial community is of great importance for the crop development. However, the methods of control, chemical (methyl bromide) and physical (soil solarization), change such community. The present work aimed to study the behaviour of the community of fungi in solarized and fumigated (methyl bromide) soils. The experimental design was randomized in complete blocks, with 3 treatments (soil solarization, methyl bromide, and control) and 7 replications. The soil fungi community was evaluated in both, a quantitative and qualitative way during 3 periods (before, during and after solarization) through soil samples collected from 3 depths (0-5; 10-15, and 20-25 cm). During soil solarization, a reduction of the soil fungi community, quantitatively, occurred in all layers evaluated. However, the decrease was more significant in the superficial layer. Soil solarization also reduced the number of different species of fungi, qualitatively, but in the layer of 20-25 cm the decrease was to zero after 56 days of evaluation. The soil microbial re-colonization was quantitatively larger for the treatment with methyl bromide by comparing to the other treatments. However, qualitatively, the increase was not the same. The increase of the soil microbial recolonization in the solarized and control treatments was accompanied by diversification of fungal species.
Efeito da solarização e do brometo de metila sobre a comunidade de fungos do solo
Keywords: Microbial re-colonization; Physical control and chemical control